Sukuk: fundamental properties And perspectives of development in Kazakhstan (Journal of Economic Research & Business Administration, 2023)
The emerging and rapidly developing Islamic capital market has become an integral part of the modern financial system, providing not only Islamic but also traditional financial institutions with new market instruments for the efficient mobilization of resources and optimal allocation of assets. Sukuk, being a unique Islamic security, gives rise to discussions regarding its fundamental properties and functions, however, continues to demonstrate its dynamic development in secondary markets, which makes it the object of close attention for the economic practice of Kazakhstan, where approximately 60% of the population adheres to one degree or another Muslim faith.        In the proposed article, the authors set a goal to make a theoretical review that allows us to clarify the features of sukuk in the context of Shariah principles, compare them with the parameters of traditional bonds to identify similar and distinctive characteristics between them, and also determine the prospects for the development of sukuk in the Republic of Kazakhstan, as one of the alternative financial instruments. It is important that the use of Islamic securities allows us to adhere to the trend of the 17 UN SDGs, as well as contribute to the development of infrastructure projects, the construction and modernization of which has been updated in Kazakhstan in recent years.Key words: sukuk, financing, investment, sustainable development, Islamic financing